Change of olfactory function as a marker of inflammatory activity and disability progression in MS. (February 2019) - Bsteh, Gabriel; Hegen, Harald; Ladstätter, Felix; Berek, Klaus; Amprosi, Matthias; Wurth, Sebastian; Auer, Michael; Di Pauli, Franziska; Deisenhammer, Florian; Reindl, Markus; Berger, Thomas; Lutterotti, Andreas
Background: Impaired olfactory threshold has been reported in early inflammatory phases of MS, while impaired odor identification was associated with more widespread disability. Objective: To prospectively assess the development of olfactory function and its correlation with relapse and disability progression. Methods: In this prospective, 3-year longitudinal study on 151 MS patients and 30 healthy controls, three different qualities of olfactory function (threshold, discrimination, and identification) were quantified using the Sniffin' Sticks test. The influence of relapses and disability on olfactory function was analyzed at different time points and in a multivariate model. Results: Discrimination and identification capability significantly worsened over 3 years, while threshold did not. Threshold was markedly impaired in patients with relapse activity within 12 months, recovered in the absence of relapse, and was associated with a 2.5-fold increased risk of relapse. Deterioration of discrimination and identification was irreversible and both strongly associated with and predictive of EDSS progression. Conclusion: Olfactory function changes over time in MS. Threshold impairment is transient and predicts inflammatory disease activity, while odor identification and discrimination are associated with disability progression. Olfactory dysfunction might be a useful and easily obtainable parameter to monitor patients with regard to inflammation and neurodegeneration in MS.